Alla ricerca di una metodologia clinica condivisa: strumenti per una diagnosi affidabile - Paolo Fiori Nastro (Il sogno della farfalla, 2021)
In the international psychiatric literature, diagnosis has always been a highly debated subject since the therapeutic outcome mainly depends on a thorough and correct diagnosis. In the 20th century the evolution of new concepts and theories led to redefine the diagnostic boundaries between different mental pathologies therefore influencing the psychiatrist’s diagnostic and therapeutic practice. The benefit of psychotherapy is widely recognized but fundamentally complex remains the issue of evaluating its effectiveness as well as the quantification of the clinical improvement as a result of the therapeutic intervention. Although there is a shared agreement on the idea that all psychotherapies are equivalent in terms of effectiveness and that the therapeutic rapport’s quality is a fundamental aspect in order to achieve a positive outcome, a shared system to “measure” pathologies and their cure is still lacking today. The author underlines the need to create debating opportunities among colleagues to deepen the clinical practice’s study in order to identify the shared methodological and practical approaches based on the Collective Analysis history.